Achievable outcomes of dynamic contribution games - Steven A. Matthews (Theoretical Economics, 2013)
This paper concerns multistage games, with and without discounting, in which each player can increase the level of an action over time so as to increase the other players' future payoffs. An action profile is said to be achievable if it is the limit point of a subgame perfect equilibrium path. Necessary conditions are derived for achievability under relatively general conditions. They imply that any efficient profile that is approximately achievable must be in the core of the underlying coalitional game. In some but not all games with discounting, the necessary conditions for achievability are also sufficient for a profile to be the limit of achievable profiles as the period length shrinks to zero. Consequently, in these games when the period length is very short, (i) the set of achievable profiles does not depend on the move structure; (ii) an efficient profile can be approximately achieved if and only if it is in the core; and (iii) any achievable profile can be achieved almost instantly.
Keywords: C7; 330; Dynamic games; monotone games; core; public goods; voluntary contribution; gradualism